(untitled) (Circe de clásicos y modernos, 2018)
The sources of the “indirect tradition” of Alexander’s Lives (βίοι) are distinguished among those more credible, framed within the limits of imperial historiography and biography, and those of invention, closer to the travel novels and paradoxography. This paper attempts to go beyond these genre categories to understand the duality history / fiction as material coexisting in the different versions about the founding of Alexandria by three Greek authors of the imperial period: Anabasis of Alexander the Great by Arrian, Life of Alexander by Plutarch and The life and exploits of Alexander the Great by Pseudo-Callisthenes.